Influence of socio-demographic, socio-educational and socio-labor variables on environmental awareness and responsible consumption - Sánchez-Jiménez, Kevin (2025)
Introduction: Society's eating habits have undergone a significant change, now determined by environmental awareness and responsible consumption. Objective: This article aims to determine whether sociodemographic variables (gender, age, marital status, place of residence), socio-educational, and socio-occupational variables influence both environmental awareness and responsible consumption. Methodology: To this end, a study sample of 237 consumers from the Red Agroecológica del Austro (RAA) and 237 from AgroAzuay, two of the most representative agroecological markets in the city of Cuenca, Ecuador, was determined. For data analysis, a one-way ANOVA test was applied using the SPSS statistical software. Conclusions: Under these conditions, the research results indicate that gender, level of education, and employment status significantly influence environmental awareness, while gender, age, place of residence, and employment status significantly influence responsible consumption.